STRATEGI KOMUNIKASI DALANG COLLECTION DALAM MENSOSIALISASIKAN PROGRAM BANK SAMPAH DI KOTA PEKANBARU - Ria Risviana; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Waste is a major environmental problem faced by governments and communities in developing countries, including Indonesia. Garbage is permaslahan that can not be left alone and need to find a solution and handled well. In addressing the garbage problem needs the involvement of all stakeholders, especially the public. One of the people who care about this waste problem is Soffia Seffen, SH by establishing Dalang Collection and establish a program that is rubbish bank. Yag efforts made to introduce this program is to socialize or communicate with the public. However, there are still many people who do not know Dalang Collection and programs. This study aims to determine how the communication strategy in disseminating Dalang Collection trash bank program in the city of Pekanbaru and determines the constraints Dalang Collection in disseminating the garbage bank program in the city of Pekanbaru.This study uses a qualitative descriptive study of strategic communication models are supported by the communication strategy according Effendy. Informants in this research is the founder, employee Dalang Collection, schools (students and teachers), residential (community), and office (employees) by using purposive sampling technique. Data collection techniques using participant observation, interview and documentation.The results showed that the socialization Dalang Collection analyzing and dividing by the target. Collection mastermind requires cognitive response, conative, and affective. Factors to be considered in designing the message: the message content, message structure and message format. Communication media used the media face to face communication (presentation) and the mass media both print and electronic media locally (RTV, Riau Pos, and the Tribune). The role of communicators in the communication attractiveness (belief, charismatic, and emapatik), and the credibility of the source (skills and knowledge) in conveying the message.Key words : Communiction strategy, socialize, bank of garbageJom